Family-Centered Practices and Caregiver Mental Health in a Developmental Intervention for Young Children With Congenital Zika Syndrome. Issue 1 (January 2023) - Williams, Natalie A.; Villachan-Lyra, Pompéia; Hatton-Bowers, Holly; Marvin, Christine; Chaves, Emmanuelle; Hollist, Cody; Gomes, Renata Trefiglio Mendes; Barbosa, Leopoldo Nelson F.
Abstract : The goal of this study was to describe the provision of intervention services to children with congenital Zika syndrome (CZS) in a large health care institution located in Recife, Brazil, and family factors related to intervention involvement, through the lens of family-centered developmental–behavioral pediatric care principles. Caregivers ( N = 50) of children with CZS who were receiving services at a public rehabilitation hospital participated a cross-sectional survey study. Among caregivers, 22% reported a low number of both child and caregiver intervention contacts, 26% reported a high number of child contacts but low caregiver contacts, and 52% reported both high child and caregiver contacts with intervention staff in the past 3 months. Caregiver stress scores were higher and coping strategies were lower in the low child and caregiver intervention contact group. Most caregivers reported high levels of family-centered practices. In regression models, low family resources was associated with higher depression and stress and low coping strategy use, whereas higher support was associated with higher coping. This study adds to the small literature exploring intervention services provided to children with CZS with a particular emphasis on family-centered care principles. It is recommended that intervention programs in Brazil evaluate the availability and accessibility of family resources and develop strategies to help connect families to resources that promote caregiver mental health and child outcomes.